Descriptive analysis of COVID-19 patients in the context of India. Issue 3 (3rd April 2021) - Bhatnagar, Vaibhav; Poonia, Ramesh Chandra; Nagar, Pankaj; Kumar, Sandeep; Singh, Vijander; Raja, Linesh; Dass, Pranav
Abstract: COVID-19 is now becoming a global issue and declared as pandemic by world health organization. This virus spread out from China to entire world. This paper performed a descriptive analysis of COVID-19 in special reference of India. Different attributes such as age, gender, travel history, communication type and current status are analyzed. Till now it can be stated from the study that age is not a significant factor that affect a person to be captured by this disease, also age attribute is normally distributed in current dataset. A significant relationship is found between gender (male and female) and Transmission Type (imported from other country or communicated from local) of the patients.